THE EFFECTIVENESS OF STORY TELLING TO IMPROVE STUDENT’S SPEAKING SKILLS AT THE TENTH GRADE OF SMA GAJAH MADA BANDAR LAMPUNG - Exglard, iradnaluwiner (Journal of Education, Linguistics, Literature and Language Teaching, 2024)
Speaking is the first method for communicating with people in a social group. The storytelling technique helps students' speaking skills abilities by expanding their vocabulary, developing creativity, improving pronunciation, and organizing thoughts. This study aims to 1) determine whether Storytelling is compelling to speaking skills in the tenth grade of SMA Gajah Mada Bandar Lampung and 2) to understand how the storytelling method is applied in learning English in class X SMA Gajah Mada Bandar Lampung. This research used quantitative research as "an approach to objectively testing the theory by examining the relationships between variables. These variables can be monitored with tools, and the resulting numerical data can be statistically analyzed. Data was collected using pretest, post-test, and comparison of experimental and control classes. The results demonstrated that students' speaking skills improved following Storytelling, and students' speaking abilities improved significantly. Storytelling helped students express themselves, strengthen their communication capacity, and enhance their understanding, fluency, vocabulary, grammar, and pronunciation.